2014
DOI: 10.1002/mgg3.57
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal microarray analysis as a first‐tier clinical diagnostic test: Estonian experience

Abstract: Chromosomal microarray analysis (CMA) is now established as the first-tier cytogenetic diagnostic test for fast and accurate detection of chromosomal abnormalities in patients with developmental delay/intellectual disability (DD/ID), multiple congenital anomalies (MCA), and autism spectrum disorders (ASD). We present our experience with using CMA for postnatal and prenatal diagnosis in Estonian patients during 2009–2012. Since 2011, CMA is on the official service list of the Estonian Health Insurance Fund and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 34 publications
0
23
1
Order By: Relevance
“…As providers move to molecular genetics approaches, the residual risk will be significantly increased. One of the largest prenatal CMA studies found that the frequency of pathogenic or likely pathogenic Copy Number Variants (CNVs) detectable by CMA in women with normal karyotypes and anatomically normal fetuses is 1.65% (1/61) and other smaller studies of fetuses with normal ultrasound results report supporting values . Based on the available data, some professional bodies, such as ACOG, recommend that ‘chromosomal microarray analysis be made available to any patient choosing to undergo invasive diagnostic testing’ .…”
Section: Discussionmentioning
confidence: 99%
“…As providers move to molecular genetics approaches, the residual risk will be significantly increased. One of the largest prenatal CMA studies found that the frequency of pathogenic or likely pathogenic Copy Number Variants (CNVs) detectable by CMA in women with normal karyotypes and anatomically normal fetuses is 1.65% (1/61) and other smaller studies of fetuses with normal ultrasound results report supporting values . Based on the available data, some professional bodies, such as ACOG, recommend that ‘chromosomal microarray analysis be made available to any patient choosing to undergo invasive diagnostic testing’ .…”
Section: Discussionmentioning
confidence: 99%
“…Multiple LCSHs on different chromosomes that indicate close parental consanguinity, as well as LCSHs that cover the majority of single chromosomes and are caused by UPD, have been studied during the last few years, and their clinical implications are, therefore, better understood [Papenhausen et al, 2011;Wang et al, 2015]. Single LCSHs in patients without parental consanguinity are not infrequently found during routine diagnostics in centers where SNP array technology is in use, but their clinical significance remains unclear in most of the cases [Zilina et al, 2014]. Reporting a variant of uncertain significance (VUCS) can cause anxiety in patients and frustration in referring doctors who are not specialists in the field of medical genetics [Coughlin et al, 2012;Zilina et al, 2014].…”
Section: Discussionmentioning
confidence: 99%
“…Single LCSHs in patients without parental consanguinity are not infrequently found during routine diagnostics in centers where SNP array technology is in use, but their clinical significance remains unclear in most of the cases [Zilina et al, 2014]. Reporting a variant of uncertain significance (VUCS) can cause anxiety in patients and frustration in referring doctors who are not specialists in the field of medical genetics [Coughlin et al, 2012;Zilina et al, 2014]. Therefore, it is of great importance to work toward minimizing the number of reported VUCSs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, it was observed that many of the ASD‐associated genes detected using WES were linked with the fragile X protein and involved in synaptic plasticity (Iossifov et al, 2012). On the other hand, chromosomal microarray analysis is a cytogenetic assay used for the detection of chromosomal abnormalities in patients diagnosed with ASD (Zilina et al, 2014). Among these abnormalities, it was found that GABA receptor subunit genes GABRB3, GABRA5 and GABRG3 were closely associated with the pathophysiology of ASD (Kim et al, 2006; Klauck, 2006; Vorstman et al, 2006).…”
Section: Causes Of Asdmentioning
confidence: 99%